Vattengeokemi och syre-väteisotoper som verktyg för spårning av vattenkällor vid vattentäkter : En fältstudie vid Gäddviksområdet i Luleå - Eriksson Solander, Viktor (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2020)
Groundwater is an important source of drinking water where advanced knowledge in the area is of great importance in order to ensure the drinking water quality for future generations. Groundwater is chemically complex because it is formed from a large variety of water sources where the water comes from and passes through different geological and hydrological environments. Environmental forensics is an important area in environmental studies where a wide variety of analytical techniques are integrated to be able to trace and identify sources of pollution. In the Gäddvik project, environmental forensics is applied as a method for tracking pollution in naturally occurring waters. Concentrations of selected elements, oxygen- and hydrogenisotopes and cerium-anomalies have been used to show chemical differences between different water sources in groundwater reservoirs in the Gäddvik area. A sub-study at Kvarnträsket (a lake located in the Gäddvik area) has been carried out to track surface water intrusion in nearby groundwater used for drinking water. Different types of graphs and charts have been created from data on the area, where these have been used to give a simplified visualization of different geochemical trends for selected elements/isotopes. Quality differences between two nearby groundwater reservoirs have been studied and discovered, where one is Luleå’s main groundwater reservoir and the other is a backup groundwater reservoir. Surface water from the Luleå River has been detected in the main groundwater reservoir to a greater extent than in the backup groundwater reservoir. This may be since the main reservoir is under higher exposure and uses river water for artificial infiltration to the groundwater. Oxygen- and hydrogenisotopes have been shown to be useful for tracking and locating surface water infiltration in groundwater intended for drinking water. Grundvatten är en viktig källa för dricksvatten där en utvecklad kunskap inom området är av stor betydelse för att kunna säkerställa ...